Cost-effectiveness of treatment in adults with blood pressure of 130–139/80–89 mmHg and high cardiovascular risk in China: a modelling studyResearch in context - Jiangtao Li; Dong Zhao; Jun Cai; Shuohua Chen; Shouling Wu; Yue Qi (The Lancet Regional Health. Western Pacific, 2024)
Summary: Background: The most recent updated hypertension guidelines recommend individuals with systolic blood pressure (SBP)/diastolic blood pressure (DBP) of 130–139/80–89 mmHg and high cardiovascular risk should receive antihypertensive drug treatment. This study aimed to assess the benefits and cost-effectiveness of medication for people aged ≥35 years with this blood pressure stratum and high cardiovascular risk in China. Methods: The benefits of drug treatment in adults aged ≥35 years with SBP/DBP of 130–139/80–89 mmHg and high cardiovascular risk were evaluated in decision-analytic simulation models. Decreasing numbers of cardiovascular disease (CVD) events and premature deaths from all causes and increasing quality-adjusted life-years (QALYs) from drug treatment were estimated in 10-year and lifetime horizons. The incremental cost-effectiveness ratios (ICER) for drug treatment were calculated. Findings: Among approximately 106.60 million Chinese adults aged ≥35 years with this blood pressure stratum and high cardiovascular risk, drug treatment was estimated to prevent 2,060,000 strokes and 660,000 myocardial infarctions over a 10-year time horizon. Adults prescribed antihypertensive drugs could gain 0.034 incremental QALYs. Over a lifetime horizon, adults who start treatment earlier could benefit more in preventing CVD and gaining incremental QALYs. The medication treatment is cost-effective either over a 10-year time horizon with an ICER of Int$13321.29 per QALY gained or over the remaining lifetime. Interpretation: Antihypertensive treatment of adults with SBP/DBP of 130–139/80–89 mmHg and high cardiovascular risk would gain substantial benefits with cost-effectiveness. The young and middle-aged population would derive the most benefit. Funding: National Natural Science Foundation of China, and Beijing Natural Science Foundation.